Patent Filing in India: A Quantitative Analysis - Vijayakumar, M. (Journal of Information and Knowledge, 2015)
A study was performed to assess the quantitative trend of patent filing in India throughout 2005-06 to 2009-10. Year wise growth, geographical wise contribution, subject wise distribution of patent filing in India were presented.